Tumor Flare Reaction in a Classic Hodgkin Lymphoma Patient Treated With Brentuximab Vedotin and Tislelizumab: A Case Report - Zhu, Chunting; Zhao, Yi; Yu, Fang; Huang, Weijia; Wu, Wenjun; He, Jingsong; Cai, Zhen; He, Donghua (Frontiers in Immunology, 2022)
Background: Tumor flare reaction (TFR) is a clinical syndrome, which is mainly associated with painful and swollen lymph nodes or splenomegaly, slight fever, bone pain, and skin rash during treatment with immune-related drugs, causing difficulty in distinguishing TFR from disease progression. Brentuximab vedotin (BV) and programmed death 1 (PD-1) inhibitor are two ideal drugs used for the treatment of classic Hodgkin lymphoma, but few studies have reported their adverse effects in association with TFR. The efficacy and safety of monotherapy or combination therapy with these drugs needs to be further evaluated. It is essential to determine whether treated patients can develop TFR, thus enabling more accurate diagnosis and treatment. Case presentation: A 26-year-old female patient, diagnosed with classic Hodgkin lymphoma, had received 2+3 cycles of ABVD chemotherapy (a combination of adriamycin, bleomycin, vinblastine and dacarbazine) and 4 cycles of PD-1 inhibitor (tislelizumab) therapy but exhibited poor efficacy. Subsequently, she was given combination therapy of BV (100 mg) + tislelizumab (200 mg). However, a slight fever, painful and swollen axillary lymph nodes, multiple skin rashes with pruritus, joint pain, fatigue with poor appetite appeared during the treatment. Ultrasound (US) scans revealed that multiple lymph nodes were significantly enlarged. After treatment with low-dose dexamethasone and cetirizine, the symptoms were alleviated. A biopsy of the left axillary lymph node revealed that lymphoid tissue exhibited proliferative changes, without tumor cell infiltration. These findings were consistent with the clinical and pathological manifestations of TFR. Conclusion: Combination therapy with BV and PD-1 inhibitor was effective in the treatment of relapsed or refractory classic Hodgkin lymphoma. The results suggest that the combination therapy may cause TFR, and biopsy as well as continuous imaging observation are important to determine the disease stage. This approach allows clinicians to decide whether to continue the current treatment plan, and alerts them to the occurrence of excessive activation of the immune system.